RESEPSI DAN TRANSFORMASI ISTILAH ΔΟῦΛΟΣ ΧΡΙΣΤΟῦ (DOULOS CHRISTOU) DALAM KONTEKS SOSIAL-EKONOMI ABAD PERTAMA - Budirahardjo, Yuki; Rimun, Robinson (TEOLOGIS, RELEVAN, APLIKATIF, CENDIKIA, KONTEKSTUAL, 2026)
This study examines the Greek term δοῦλος Χριστοῦ (“servant/slave of Christ”) as it appears in Paul’s letters, by exploring its socio-economic context, contextual reception, and theological transformation. Using a qualitative methodology with historical-sociological and textual-exegetical approaches, the research reconstructs the reality of slavery in the Greco-Roman and Jewish worlds of the first century while analyzing how Paul reinterpreted this symbol. The findings indicate that δοῦλος in the Roman context denoted a degraded status without civil rights, whereas in the Jewish tradition it carried an honorable nuance as the designation “servant of the Lord.” Paul transformed this term into a paradoxical identity of faith: what was considered lowly was elevated as a sign of spiritual freedom, loyalty, and devotion to Christ. The analysis of verbal aspects highlights the dual dimension of this identity—both a definitive, once-for-all decision (aorist) and an ongoing lifestyle of service (present). The study concludes that δοῦλος Χριστοῦ is not merely Paul’s personal label, but a subversive symbol that shaped the identity, spirituality, and egalitarian relationships of the early Christian community. Further research is recommended to investigate the reception of this term in other New Testament writings and early Christian literature.